Diversidade de genótipos de goiabeiras por caracteres vegetativos e reprodutivos - Silva, Séphora Neves da (2017)
The guava crop yield is influenced by plant flowering and fruiting stages. Additional knowledge is needed on the diversity of guava genotypes during the vegetative and reproductive stages as well as on pollen viability. This information will help to identify crop management practices aiming to improve fruit production and quality. This information can also be used in breeding programs in the selection of high quality genotypes. The objective of this work was to investigate the diversity of guava genotypes, expressed by vegetative and reproductive characteristics during the crop cycle in two pruning seasons, as well as to study pollen viability under different growing seasons and locations. The guava genotype diversity was verified by the temporal evaluation of seven vegetative characters and eight reproductive traits for 22 genotypes and two production pruning: summer and winter. In addition, the crop diversity was also assessed using microsatellite markers and based on the occurrence of pests and diseases in the field. Cluster analyzes were used to identify patterns of vegetative and reproductive plant behavior, possible pest and disease resistance and molecular polymorphisms. The genetic diversity, evaluated though molecular markers, allowed the identification of similar genetic and morphological patterns for the genotypes Cortibel 7 and 8, which were the most similar among all guava genotypes. The genotypic behavior was influenced by the pruning period. The genotype Cortibel 8 showed a short flowering cycle and large fruit sizes for the two pruning periods. Cortibel 11 showed a possible resistance to pests and diseases. The pollen viability was obtained using colorimetric methods for the 22 genotypes during two growing seasons and two locations. Genetic parameters were estimated using mixed models. The genotype pollen viability was high and influenced by the environment conditions during the first growing seasons. Overall, those results provide relevant information for the guava crop, considering the importance of the reproductive and fruit quality parameter evaluated.